(untitled) (Research, Society and Development, 2020)
Objective: To evaluate the effects of the safflower oil supplementation on the body composition and biochemistry parameters of exercised rats. Methods: Forty male rats were divided into four groups: sedentary control, exercised control, sedentary safflower oil and exercised safflower oil. The exercise performed for treadmill running for four weeks. It was measured the murinometry of the animals, consumption, protein, carcass fat, liver fat, abdominal fat and biochemical parameters. As statistical analyzes were done, use the Anova test followed by Tukey, with p <0.05. Results: The group of safflower oil exerted positive responses regarding the parameters, such as reduction of food consumption, body weight, body mass index, abdominal and total fat. The sedentary safflower oil group had a higher hepatic fat (P <0.05) and an increase in total cholesterol (P <0.05). All groups had a reduction in plasma triglyceride levels when compared to the control group (P <0.05). Conclusion: The consumption of safflower oil induces beneficial results in body composition associated with physical training. When safflower oil is consumed without physical exercise, it can trigger an increase in serum cholesterol and fatty liver.